2016
DOI: 10.14693/jdi.v23i2.1000
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and quality of life among elderly in Thai

Abstract: Oral health contributes physically and psychologically to quality of life. Objective: To investigate the relationship of oral health status with oral health related and general Quality of Life (QOL) in elderly. Methods: Subjects were 612 community dwelling Thai aged 60 years or older. A questionnaire was evaluate socio-demographics, general oral health assessment index (GOHAI) and world health organization quality of life (WHOQOL). Oral examinations assessed teeth present, decayed teeth, gingival bleeding, poc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
5
6
1
1
Order By: Relevance
“…The results of this study also agreed that there exists a need to provide the public with suitable educational materials related to the oral cancer issue [18]. The elderly population is considered to be a high-risk population in this regard, since they may have decreasing cognitive function, limited access to health information and health facilities, as well as low health literacy [24,25]. The involvement of healthcare workers and caregivers may therefore help in increasing the level of knowledge among the elderly [28][29][30].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The results of this study also agreed that there exists a need to provide the public with suitable educational materials related to the oral cancer issue [18]. The elderly population is considered to be a high-risk population in this regard, since they may have decreasing cognitive function, limited access to health information and health facilities, as well as low health literacy [24,25]. The involvement of healthcare workers and caregivers may therefore help in increasing the level of knowledge among the elderly [28][29][30].…”
Section: Discussionsupporting
confidence: 64%
“…However, it has previously been shown that people of an older age tend to have poorer knowledge about oral cancer [19]. The limited extent to which the elderly are exposed to public media and the internet as well as their lack of access to health facilities, relatively low quality of life, and low level of health literacy may have contributed to the results [19,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the studies showed that the number of FTUs positively affected the ability to masticate. 10,11 Similar research conducted by Shakina et al 13 and Adhiatman et al 14 states that there is no a significant relationship between tooth loss and nutritional status.…”
Section: Introductionmentioning
confidence: 71%
“…The influence of FTUs on BMI is supported by research conducted by Indrasari et al 10 that explains that FTUs are related to the ability to masticate -the higher the FTU value, the better the ability to masticate and vice versa. Good mastication is obtained when the minimum number of FTUs in the oral cavity is 7.5.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation